Integrating single-cell sequencing and transcriptome analysis to unravel the mechanistic role of sialylation-related genes in sepsis-induced acute respiratory distress syndrome - Liu, Xiaobing; Huang, Yake; Zhang, Hao; Yang, Xia; Liu, Quanxing; Dai, Jigang (Frontiers in Immunology, 2025)
BackgroundStudies have shown that sialylation of C1 esterase inhibitors is crucial for their interaction with histones, and histone-C1 esterase inhibitor complexes are detected in acute respiratory distress syndrome (ARDS), suggesting a potential role of sialylation in ARDS. However, the specific function of sialylation in ARDS remains unclear. Therefore, this study aimed to investigate the mechanism of sialylation-related genes (SRGs) in sepsis-induced ARDS.MethodsThe ARDS related datasets (GSE32707, GSE66890, and GSE151263) were included in this study. Candidate genes were identified by implementing differential expression analysis and weighted gene co-expression network analysis (WGCNA). Subsequently, further selection by machine learning and expression assessment confirmed the key genes related to sialylation in sepsis-induced ARDS. Following this, the predictive ability of key genes as a whole for sepsis-induced ARDS was evaluated by creating a nomogram model. Afterwards, enrichment analysis, construction of regulatory networks, and drug prediction analysis were implemented to further understand the molecular mechanisms of action of key genes. Furthermore, single-cell RNA sequencing (scRNA-seq) data analysis was conducted to obtain key cells. Additionally, cell communication and pseudo-time analyses were implemented. In the end, the expression levels of the key genes were assessed by collecting clinical samples.ResultsCD19 and GPR65 were identified as key genes associated with sialylation in sepsis-induced ARDS. The constructed nomogram model demonstrated that CD19 and GPR65 as a whole exhibited robust predictive capability for sepsis-induced ARDS. Meanwhile, CD19 and GPR65 were also found to be significantly co-enriched in the apoptosis and B-cell receptor signaling pathway. In addition, some important regulators and drugs with targeting effects on key genes were predicted, such as NEAT1, OIP5-AS1, alprostadil, and tacrolimus. Further, the scRNA-seq data analysis identified nine cell types, among which CD14 monocytes (CD14Mono) was designated as the key cell. Importantly, GPR65 expression exhibited dynamic changes during differentiation of CD14Mono. Also, we found that CD19 was significantly up-regulated in ARDS group.ConclusionWe identified CD19 and GPR65 as key genes associated with sialylation in sepsis-induced ARDS, highlighting CD14Mono as key cell type implicated in sepsis-induced ARDS. These findings offered theoretical support for understanding the mechanism of sialylation on sepsis-induced ARDS.